Research Methodology Advanced Techniques with Statistical Methods - Singh,G.B. (Jaipur Paradise, 2022)
The basic objective of writing this book is to acquaint the reader with enough fundamental issues relating to different techniques of research methodology. The book is designed to provide not only the knowledge of research methodology but also an understanding of the major business problems.